2022
DOI: 10.18632/aging.204393
|View full text |Cite
|
Sign up to set email alerts
|

The potential benefit of metformin to reduce delirium risk and mortality: a retrospective cohort study

Abstract: Purpose: Metformin has been reported to improve age-related disorders, including dementia, and to lower mortality. This study was conducted to investigate whether metformin use lower delirium risk, as well as longterm mortality. Methods: In this retrospective cohort study, previously recruited 1,404 subjects were analyzed. The relationship between metformin use and delirium, and the relationship between metformin use and 3-year mortality were investigated. Main findings: 242 subjects were categorized into a ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 59 publications
1
7
1
Order By: Relevance
“…Our group also confirmed that inpatients using metformin had improved three-year survival rates compared to non-metformin users [12]. In addition, our data also showed that prevalence of delirium was lower among those who were on metformin compared to those without [12].…”
Section: Introductionsupporting
confidence: 81%
See 3 more Smart Citations
“…Our group also confirmed that inpatients using metformin had improved three-year survival rates compared to non-metformin users [12]. In addition, our data also showed that prevalence of delirium was lower among those who were on metformin compared to those without [12].…”
Section: Introductionsupporting
confidence: 81%
“…Also, agedependent, dose-dependent, and gender-dependent variable effects on lifespan were reported in mice [27,28]. Although these previous studies' results are not consistent, our cohort mentioned above (from which the present data are an analysis of its subgroup) clearly showed a positive influence of metformin use on survival among diabetic inpatients [12].…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Another theory for the development of delirium is a decreased activity of the brain insulin signaling system, mainly due to central insulin resistance and insulin de ciency. Intranasally administered insulin (INI) can restore the activity of the brain insulin system, has a wide therapeutic prospect for delirium [21].In 2022, a retrospective cohort study (include 1404 subjects) found that metformin reduced the incidence and mortality of delirium in patients with diabetes mellitus [22].…”
Section: Discussionmentioning
confidence: 99%